Spark plasma sintering of bulk MgB2 and levitation force measurements. (7th January 2020) - Noudem, J G; Bernstein, P; Dupont, L; Martin, F G R; Sotelo, G G; Dias, D H N; de Andrade, R; Muralidhar, M; Murakami, M
Abstract: We present preliminary results suggesting that MgB2 is a superconductor that could be used in Maglev vehicles. For this purpose, we compare the levitation capability of MgB2 samples to those of YBCO bulks.